A composite material with core-shell heterostructure and its preparation method and use

CN118788400BActive Publication Date: 2026-10-13JISHOU UNIVERSITY
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202411088133.9
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-08-08
Publication Date
2026-10-13
Estimated Expiration
2044-08-08

AI Technical Summary

Technical Problem

[0004]针对现有技术存在单一钙钛矿材料光催化效率低以及光吸收范围有限、载流子分离低、材料间界面接触不理想以及表面暴露活性位点有限等问题,本发明提供了一种具有核壳异质结构的复合材料及其制备方法和用途,通过采用原位生长的方式,将共价或氢键有机框架类材料(还包括它们的衍生物或类似物)与氧化物或硫化物钙钛矿类材料(还包括它们的衍生物或类似物)进行结合,利用有机框架材料中的碳和/或氮元素与钙钛矿材料中的金属元素之间形成键合作用(包括但不限于化学键或配位键等),进而提高界面接触,实现钙钛矿与有机框架材料的原位包裹,有效地促进了光生载流子的分离效率,克服了现有单一钙钛矿材料光催化效率低的不足

Benefits of technology

[0041]与现有技术相比较,本发明的有益技术效果如下所述:

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118788400B_ABST
    Figure CN118788400B_ABST
Patent Text Reader

Abstract

The application discloses a kind of composite materials with core-shell heterostructure and preparation method and purposes thereof, belong to inorganic functional material preparation technical field.By bonding effect in situ wrapping a layer of adjustable thickness organic framework material on perovskite, a kind of composite materials with core-shell heterostructure is prepared, and the composite material is applied to environmental purification and artificial photosynthesis of hydrogen peroxide.In the synthesis process of the composite material, carbon and / or nitrogen element in organic framework material and metal element in perovskite material form bonding effect, and then realize in situ wrapping of perovskite and organic framework material, optimize the interface contact quality of material, effectively promote the separation and transmission of photo-generated charge, with the advantages of low cost, convenient operation, short cycle, batch preparation and the like.In addition, the composite material also has excellent photocatalytic performance, especially in photocatalytic synthesis of hydrogen peroxide, photocatalytic degradation of antibiotic or dye molecule, photocatalytic indoor formaldehyde oxidation and other fields has its unique advantages, and is expected to expand new research direction and lay a solid foundation for the advanced development of photocatalytic material for environmental purification.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to inorganic functional composite materials, specifically to a composite material with a core-shell heterostructure, its preparation method, and its applications, belonging to the field of photocatalytic materials technology. Background Technology

[0002] Perovskite materials, due to their diverse structures, simple preparation processes, low cost, strong photovoltaic properties, and excellent physicochemical properties, are a class of semiconductor materials with excellent optoelectronic properties and have attracted widespread attention from scholars. Currently, they have shown promising application prospects in energy, environment, electronics, optoelectronics, catalysis, and other fields. Angew. Chem. Int. Ed. 2020, 59, 136-152; Adv. Mater. 2022, 34, 2105635; Adv. Funct. Mater. 2023, 33,2301981; Nat. Electron. 2024, 7, 216-224). However, single perovskite materials also have many drawbacks, such as: poor charge separation and a large band gap in single oxide perovskite materials, resulting in a small light absorption range and low solar energy utilization, which limits their applications. Single sulfide perovskite materials have excessively narrow band gaps, limiting their solar energy utilization and thus restricting their applications. Small 2021, 17, 2005345; Angew. Chem. Int. Ed. 2023, 135,e202215700; Nano Res. 2023, 16, 7867-7873; Adv. Funct. Mater. (2024, 34, 2309514). To address these shortcomings, scientists have employed methods such as morphology control, elemental doping, supported catalysts, and interface design to overcome the limitations of perovskite materials. While effective composite material design demonstrates significant advantages in improving charge separation and enhancing solar energy utilization, mechanically mixed materials suffer from suboptimal interfacial contact, limiting charge separation and resulting in low photocatalytic efficiency.

[0003] Existing chalcogenide perovskite functional materials suffer from limitations such as limited light absorption range, low carrier separation, suboptimal interfacial contact, and limited exposed active sites. To address these issues, researchers are developing new modification techniques and methods, but some shortcomings remain. For example, composites combining perovskite with traditional oxides exhibit low specific surface area, limited pore size, and poor charge transport capacity; composites combining perovskite with metal-organic frameworks suffer from poor stability, complex synthesis processes, unsuitability for mass production, poor reproducibility, and poor conductivity, significantly limiting photogenerated carrier transport and consequently reducing photocatalytic reaction rates. J. Am. Chem. Soc.2021, 143, 14253-14260; J. Am. Chem. Soc. 2024, 146, 3303-3314). Summary of the Invention

[0004] To address the problems of low photocatalytic efficiency, limited light absorption range, low carrier separation, unsatisfactory interfacial contact, and limited surface-exposed active sites in existing technologies using single perovskite materials, this invention provides a composite material with a core-shell heterostructure, its preparation method, and its applications. By employing an in-situ growth method, covalent or hydrogen-bonded organic framework materials (including their derivatives or analogs) are combined with oxide or sulfide perovskite materials (including their derivatives or analogs). The bonding (including but not limited to chemical bonds or coordination bonds) between carbon and / or nitrogen elements in the organic framework material and metal elements in the perovskite material improves interfacial contact, achieving in-situ encapsulation of the perovskite and organic framework materials. This effectively promotes the separation efficiency of photogenerated carriers, overcoming the shortcomings of low photocatalytic efficiency in existing single perovskite materials.

[0005] To achieve the above-mentioned technical objectives, the technical solution adopted by the present invention is as follows: According to a first embodiment of the present invention, a composite material having a core-shell heterostructure is provided: A composite material with a core-shell heterostructure, comprising a core and a shell encasing the core: Wherein: the core material comprises oxide perovskite or sulfide perovskite or their derivatives or similar. The shell layer comprises covalent organic framework materials or hydrogen-bonded organic framework materials or their derivatives or similar.

[0006] Preferably, the core material is selected from Bi3TiNbO9, Bi2MoO6, and Bi4Ti3O. 12 Bi2WO6, BiVO4, Bi5FeTi3O 15 BiFeO3, Bi7Fe3Ti3O 21 One or more of BaZrS3, SrZrS3, CaZrS3, CaTiS3, BaTiS3, and SrTiS3, preferably Bi3TiNbO9, Bi2MoO6, or Bi4Ti3O 12 BiVO4, Bi5FeTi3O 15 One or more of BaZrS3, SrZrS3, BaTiS3, and CaZrS3, more preferably Bi3TiNbO9, BiVO4, or BaTiS3.

[0007] Preferably, the shell is selected from C4N, TpPa-COFs, and COFs.Bpy One or more of TTA-BPDA-COFs, BT-COFs-1, COFs-5, HOF-TCPB-373, HOF-PFC-1, and HOF-H4TBAPy, preferably C4N, TpPa-COFs, or COFs. BPy One or more of TTA-BPDA-COFs, more preferably C4N or TpPa-COFs.

[0008] Preferably, the composite material is Bi3TiNbO9 / C4N, Bi2MoO6 / TpPa-COFs, or Bi4Ti3O 12 / TpPa-COFs, BiVO4 / C4N, Bi5FeTi3O 15 / C4N、SrZrS3 / C4N、BaZrS3 / COFs BPy One or more of CaZrS3 / TTA-BPDA-COFs, preferably Bi3TiNbO9 / C4N or Bi4Ti3O 12 / TpPa-COFs, BiVO4 / C4N, Bi5FeTi3O 15 One or more of / C4N, more preferably Bi3TiNbO9 / C4N or BiVO4 / C4N.

[0009] Preferably, in the composite material, the composite molar ratio of the core material to the shell layer is 1:0.5~10, more preferably 1:1~8, and even more preferably 1:2~5.

[0010] Preferably, the particle size of the composite material is 0.1~10μm, more preferably 0.3~8μm, and even more preferably 0.5~5μm.

[0011] According to a second embodiment of the present invention, a method for preparing a composite material having a core-shell heterostructure is provided: A method for preparing a composite material with a core-shell heterostructure, or a method for preparing a composite material with a core-shell heterostructure as described in the first embodiment, the method comprising: 1) Prepare a shell precursor solution according to the specific composition of the target covalent organic framework material or hydrogen-bonded organic framework material (including but not limited to its analogues or derivatives) as the shell.

[0012] 2) Add oxide perovskite or sulfide perovskite (including but not limited to their analogues or derivatives) as core material to the above shell precursor solution. After the mixture is evenly dispersed, carry out a hydrothermal reaction. After the reaction is completed, purify and dry the resulting solid product to obtain the target composite material.

[0013] Preferably, step 1) specifically involves: dissolving the carbon source, nitrogen source, and reducing agent in a solvent according to the specific composition of the target covalent organic framework material or hydrogen-bonded organic framework material (including but not limited to its analogues or derivatives) used as the shell layer, and mixing them evenly to obtain the shell precursor solution. The molar ratio of the carbon source, nitrogen source, and reducing agent is 1~2:1~3:0~2.

[0014] Preferably, the carbon source includes one or more of the following: cyclohexanehexaone octahydrate (CAS: 527-31-1), 1,3,5-tricarboxymethyl phloroglucinol (CAS: 34374-88-4), 2,3,6,7,10,11-hexahydroxytriphenyl (CAS: 4877-80-9), 2-hydroxy-1,3,5-benzenetrialdehyde (CAS: 81502-74-1), and 1,3,6,8-tetra(4-carboxyphenyl)pyrene (CAS: 933047-52-0).

[0015] Preferably, the nitrogen source includes one or more of p-phenylenediamine (CAS: 106-50-3), 3,3',4,4'-biphenyltetramine (CAS: 91-95-2), [2,2'-bipyridine]-5,5'-diamine (CAS: 91-95-2), 2,2'-bipyridine-5,5'-dicarboxaldehyde (CAS: 135822-72-9), and 1,4-phenylenediboronic acid (CAS: 4612-26-4).

[0016] Preferably, the reducing agent includes one or more of hydrazine hydrate, Na2SO3, H2C2O4, FeSO4, NaBH4, KBH4, and acetic acid.

[0017] Preferably, the solvent includes one or more of ethylene glycol, DMF, deionized water, ethanol, methanol, tetrahydrofuran, dichloromethane, chloroform, N-methyl-2-pyrrolidone, dimethyl sulfoxide, toluene, trimethyltoluene, 1,4-dioxane, and acetonitrile.

[0018] Preferably, in step 2), the amount of core material added is such that the molar ratio of oxide perovskite or sulfide perovskite (including but not limited to their analogues or derivatives) to covalent organic framework material or hydrogen-bonded organic framework material (including but not limited to their analogues or derivatives) is 1:0.8~12, preferably 1:1.2~10, and more preferably 1:2.2~8.

[0019] Preferably, in step 2), the temperature of the hydrothermal reaction is 100~300℃, more preferably 120~250℃, and even more preferably 150~200℃. The time of the hydrothermal reaction is 2~48h, more preferably 5~36h, and even more preferably 8~24h.

[0020] In this invention, an in-situ growth method is used to grow covalently or hydrogen-bonded organic framework materials (organic framework materials (including but not limited to their derivatives or analogues) are a new type of crystalline porous polymer material composed of organic molecules connected by covalent bonds, which have diverse structures, ordered pore structures, good stability, large specific surface area, low density, and excellent visible light absorption capabilities, etc.). Adv. Mater. 2023, 35, 2305397; Angew. Chem. Int. Ed. 2023, 62, e202308980; Adv. Funct. Mater. 2023, 33, 2304990; J. Am. Chem. Soc 2023, 145, 19877-19884; Adv. Mater. (2024, 36, 2311042) This invention combines perovskite with oxide or sulfide perovskite materials, utilizing the bonding (including but not limited to chemical bonds or coordination bonds) between carbon and / or nitrogen elements in the organic framework material and metal elements in the perovskite material. This improves interfacial contact and achieves in-situ encapsulation of perovskite and organic framework material, effectively promoting the separation efficiency of photogenerated carriers. In other words, this invention develops a simple, low-cost, convenient, short-cycle, and batch-producible in-situ encapsulation strategy to achieve in-situ encapsulation of an organic framework material on perovskite, thereby preparing a batch of novel perovskite / organic framework micro / nanocomposite materials with core-shell heterostructures. These materials can be used for photocatalytic reactions and have significant innovative and scientific research value.

[0021] In this invention, perovskite oxide can be obtained commercially or prepared in-house. The preparation process is as follows: a bismuth source is mixed with one or more of a molybdenum source, tungsten source, chromium source, titanium source, niobium source, iron source, and vanadium source, along with a metal halide salt or surfactant and ethanol, and reacted (the reaction process includes, but is not limited to, grinding, hydrothermal treatment, and electrospinning). Then, optionally or not, the resulting product is placed in a calcination furnace (such as a muffle furnace) for calcination. After calcination, perovskite oxide micro / nanomaterials with regular morphology are obtained. The bismuth source is one or more of Bi₂O₃, Bi(NO₃)₃·5H₂O, BiBr₃, BiCl₃, bismuth ethoxide (C₆H₉BiO₆), and bismuth citrate (C₆H₅BiO₇). The molybdenum source is (NH₄)₆Mo₇O₇. 24 One or more of the following: ·4H₂O, Na₂MoO₄·2H₂O, and K₂MoO₄·2H₂O. The tungsten source is (NH₄)₆W₇O. 24One or more of the following: ·6H2O, Na2WO4·2H2O, and K2WO4·2H2O. The vanadium source is one or more of V2O5, NaVO3, vanadium oxalate, and vanadium acetylacetonate. The titanium source is one or more of TiO2, tetrabutyl titanate, titanium isopropoxide, and potassium titanium oxalate. The niobium source is Nb2O5 or niobium ethoxide (C). 10 H 25 One or more of NbO5 and NbCl5. The iron source is one or more of Fe(NO3)3·9H2O, FeCl3·6H2O, Fe2O3, and Fe2(SO4)3·7H2O. The metal halide salt is one or more of lithium / sodium / potassium chloride, bromide, and iodide, preferably one or more of NaCl, KCl, LiCl, NaBr, KBr, NaI, and KI. The surfactant is one or more of hexadecyltrimethylammonium bromide, hexadecylbenzyldimethylammonium bromide, and dodecyltrimethylammonium bromide. The grinding time is 0.5~10h, preferably 2~6h. The calcination temperature is 100~900℃, preferably 120~850℃. The calcination time is 1~12h, preferably 3~10h. The calcination heating rate is 2~20℃ / min, preferably 5~10℃ / min.

[0022] It should be noted that in this invention, the selection and amount of bismuth source, molybdenum source, tungsten source, vanadium source, titanium source, niobium source, and iron source are determined based on the elemental composition and stoichiometric ratio of the target oxide perovskite micro / nanomaterial. For example, when the target oxide perovskite micro / nanomaterial is Bi3TiNbO9, the raw materials to be selected are bismuth source, titanium source, and niobium source, and the amount of each added is such that the molar ratio of bismuth:titanium:niobium matches the atomic ratio in the Bi3TiNbO9 molecule.

[0023] In this invention, sulfide perovskite can be obtained commercially or prepared in-house. The preparation process is as follows: At least one of a calcium source, barium source, and strontium source, and at least one of a zirconium source and titanium salt, are mixed or dissolved and dispersed with a sulfur source, a reducing agent, and a solvent to obtain a sulfide perovskite precursor solution. Finally, a hydrothermal reaction yields sulfide perovskite micro / nanomaterials with regular morphology. The sulfur source is one or more of sulfur powder, thiourea, L-cysteine, methionine, methionine, CS2, (NH4)2S, CH3CSNH2, and Na2S2O3. The calcium source is one or more of Ca(NO3)2, CaCl2, CaI2, CaBr2, Ca(HSO3)2, and Ca(ClO)2. The zirconium source is one or more of Zr(NO3)4, Zr(SO4)2, ZrOCl2·8H2O, ZrCl4, and Zr(C6H5O7)2. The barium source is one or more of Ba(NO3)2, BaCl2, BaS, and Ba(CH3COO)2. The strontium source is one or more of Sr(NO3)2, SrCl2, SrBr2, and SrI2. The titanium salt is one or more of TiO2, tetrabutyl titanate, titanium isopropoxide, and potassium titanium oxalate. The reducing agent is one or more of hydrazine hydrate, Na2SO3, H2C2O4, FeSO4, NaBH4, KBH4, and glacial acetic acid. The solvent is one or more of ethylene glycol, DMF, deionized water, ethanol, isopropanol, methanol, tetrahydrofuran, dichloromethane, trichloromethane, and N-methyl-2-pyrrolidone. The hydrothermal reaction temperature is 100~250℃, preferably 150~220℃. The reaction time is 5~48h, preferably 8~36h. It should be noted that the selection and dosage of calcium source, zirconium source, barium source, strontium source, titanium source, and sulfur source are determined based on the elemental composition and stoichiometry of the target sulfide perovskite material.

[0024] It should be noted that the appearance morphology of the oxide perovskite micro / nanomaterials or sulfide perovskite micro / nanomaterials prepared by the present invention includes, but is not limited to, nanosheets, nanowires, nanorods, nanotubes, nanoflowers, nanospheres, nanoparticles, nanocrystals and other micromorphologies with regular shapes.

[0025] In this invention, the precursor solution of the target covalent organic framework material or hydrogen-bonded organic framework material (including but not limited to their analogues or derivatives) serving as the shell is obtained by dissolving a carbon source, a nitrogen source, and a reducing agent in a solvent in a specific ratio and mixing them uniformly according to their specific composition. For example: Preparation of C4N precursor solution: Cyclohexane hexaone octhydrate and 3,3',4,4'-biphenyltetramine were placed in a beaker according to the specified ratio. N-methyl-2-pyrrolidone and methanol solution were added, and the mixture was stirred until homogeneous to obtain the C4N precursor solution. The C4N precursor solution was then transferred to a polytetrafluoroethylene reaction liner and placed in a constant temperature drying oven for hydrothermal reaction (e.g., at 150℃ for 12 h). After the reaction was completed, the resulting mixture was filtered to obtain a solid powder. The obtained solid powder was placed in a Soxhlet extractor and extracted with tetrahydrofuran and ethanol to obtain a solid sample. Finally, the obtained solid sample was dried in a constant temperature drying oven to obtain the C4N material.

[0026] Preparation of TpPa-COFs precursor solution: p-phenylenediamine and 1,3,5-tricarboxymethyl phloroglucinol were placed in a round-bottom flask according to a specified ratio. Dichloromethane, trichloromethane, and glacial acetic acid were added and mixed thoroughly to obtain the TpPa-COFs precursor solution. The TpPa-COFs precursor solution was further stirred and reacted for a period of time. The resulting product was washed with dichloromethane at a high speed (not less than 3000 rpm), followed by multiple centrifugal washes with anhydrous ethanol. The mixture was then filtered to obtain a solid sample. Finally, the obtained solid sample was dried in a vacuum oven to obtain the TpPa-COFs material.

[0027] COFs Bpy Preparation of precursor solution: 1,3,5-tricarboxymethyl phloroglucinol and [2,2'-bipyridine]-5,5'-diamine were placed in a round-bottom flask according to the specified ratio. Dimethyl sulfoxide, acetic acid, etc. were added and mixed thoroughly to obtain COFs. Bpy Precursor solution; further COFs Bpy After the precursor solution is stirred and reacted for a period of time, the mixture is centrifuged at high speed (not less than 3000 rpm) to obtain a solid powder. The obtained solid powder is washed multiple times with tetrahydrofuran, and then washed multiple times with N,N-dimethylacetamide to obtain a solid sample. Finally, the obtained solid sample is dried in a vacuum oven to obtain COFs. Bpy Material.

[0028] Preparation of TTA-BPDA-COFs precursor solution: 2,4,6-tris(4-aminophenyl)-1,3,5-triazine and 2,2'-bipyridine-5,5'-dicarboxaldehyde were placed in a Schlenk tube according to the specified ratio. Toluene, dioxane, glacial acetic acid, etc., were added and mixed thoroughly to obtain the TTA-BPDA-COFs precursor solution. N2 was then introduced into the Schlenk tube containing the TTA-BPDA-COFs precursor solution, and the tube was placed in a constant temperature drying oven for a period of time (e.g., 72 h at 120℃). After the reaction was completed, the resulting mixture was centrifuged at a high speed (not less than 3000 rpm) to obtain a solid powder. The obtained solid powder was washed multiple times with ethanol and acetone, respectively. Finally, the obtained solid sample was dried in a vacuum oven to obtain the TTA-BPDA-COFs material.

[0029] Preparation of HOF-TCPB-373 precursor solution: 1,2,4,5-tetramethyl(4-carboxyphenyl)benzene was placed in a glass bottle with a solvent (such as DMF) in a specific ratio. The glass bottle containing the mixture was then placed in a beaker containing water to obtain the precursor solution. The obtained precursor solution was further reacted in an oven (e.g., at 100°C for 48 hours) to obtain a solid powder. The obtained solid powder was dispersed in a beaker containing ethanol, sonicated for a period of time (e.g., 30 minutes), and then allowed to stand (e.g., for 12 hours). The mixture was then centrifuged at a high speed (not less than 3000 rpm) to obtain the solid powder. Finally, the sample was dried in a vacuum oven to obtain the HOF-TCPB-373 material.

[0030] Preparation of HOF-PFC-1 precursor solution: 1,3,6,8-tetrakis(4-carboxyphenyl)pyrene was placed in a beaker according to the specified ratio, and solvent (such as DMF, methanol, water, etc.) was added. After stirring evenly, a precursor solution was obtained. The precursor solution was further stirred and reacted, and then filtered to obtain a solid powder. The obtained solid powder was washed several times with methanol. Finally, the obtained solid sample was dried (e.g., dried in a constant temperature drying oven for 12 hours) to obtain the HOF-PFC-1 material.

[0031] Preparation of HOF-H4TBAPy precursor solution: 1,3,6,8-tetra(4-carboxyphenyl)pyrene was placed in a beaker according to the specified ratio, and solvents (such as DMF, methanol, water, etc.) and reducing agents (such as acetic acid) were added and stirred until homogeneous to obtain a precursor solution; the precursor solution was further stirred and reacted, and then filtered to obtain a solid powder. The obtained solid powder was washed multiple times with water and acetone; finally, the obtained solid sample was dried (e.g., dried in a constant temperature drying oven for 12 hours) to obtain HOF-H4TBAPy material.

[0032] According to a third embodiment of the present invention, a use of a composite material having a core-shell heterostructure is provided: Use of a composite material with a core-shell heterostructure, or use of a composite material with a core-shell heterostructure as described in the first embodiment, or use of a composite material with a core-shell heterostructure prepared by the method described in the second embodiment, wherein the composite material with the core-shell heterostructure is used as a photocatalytic material.

[0033] Preferably, the composite material with a core-shell heterostructure is used for photocatalytic synthesis of H2O2, photocatalytic degradation of antibiotic or dye molecules, photocatalytic oxidation of formaldehyde, photocatalytic production of H2, and photocatalytic reduction of CO2.

[0034] In this invention, the composite material with a core-shell heterostructure is used for photocatalytic synthesis of H2O2. Specifically, a certain mass of the composite material is placed in a beaker, and a certain volume of deionized water or ultrapure water is added. After stirring and dispersing evenly, air or high-purity oxygen is introduced under dark conditions (e.g., aeration time of 0.1~4h). After stirring for a certain time (e.g., 0.1~5h), a photocatalytic reaction is carried out. After the reaction is completed, the mixture is filtered with a filter head, and the filtrate is collected. Then, a certain volume (e.g., 0.5~520mL) of the filtrate is measured and placed in a centrifuge tube. A certain concentration and volume of cerium sulfate and sulfuric acid solution are then added to the centrifuge tube for reaction. Finally, the absorbance is detected using a UV-Vis spectrophotometer to determine the photocatalytic H2O2 production performance of the material.

[0035] It should be noted that when using a composite material with a core-shell heterostructure as a reference (e.g., 1g), the volume of deionized water or ultrapure water is generally 10-2000mL. The concentration of cerium sulfate solution is 0.0001-0.003mol / L, and the volume is 1-100mL. The concentration of sulfuric acid solution is 0.1-1mol / L, and the volume is 1-80mL. Furthermore, the light treatment time is 0.1-10h, and the light intensity used is 100-300mW / cm². -2 between.

[0036] In this invention, the composite material with a core-shell heterostructure is used for photocatalytic degradation of tetracycline hydrochloride. Specifically, a certain mass (e.g., 0.005-1 g) of the composite material is placed in a photoreactor, and a certain volume (e.g., 5-50 mL) of tetracycline hydrochloride solution is added. After stirring and dispersing evenly, the mixture is stirred in the dark for a certain time (e.g., 0.1-5 h) to carry out the photocatalytic reaction. After the reaction is complete, the mixture is filtered using a filter head, and the filtrate is collected. Then, a certain volume (e.g., 0.5-20 mL) of the filtrate is measured and placed in a centrifuge tube. Finally, the absorbance is measured using a UV-Vis spectrophotometer to determine the photocatalytic degradation performance of the material for tetracycline.

[0037] In this invention, the composite material with a core-shell heterostructure is used for photocatalytic degradation of dye molecules (such as Rhodamine B) specifically as follows: A certain mass (e.g., 0.005~1g) of the composite material is placed in a photoreactor, and a certain volume (e.g., 5~50mL) of Rhodamine B solution is added. After stirring and dispersing evenly, the mixture is stirred in the dark for a certain time (e.g., 0.1~5h) to carry out a photocatalytic reaction. After the reaction is completed, the mixture is filtered with a filter head, and the filtrate is collected. Then, a certain volume (e.g., 0.5~20mL) of the filtrate is measured and placed in a centrifuge tube. Finally, the absorbance is detected using a UV-Vis spectrophotometer to determine the photocatalytic degradation performance of the material for Rhodamine B.

[0038] This invention innovatively proposes a core-shell heterostructure composite material and its novel synthesis method. Utilizing the bonding between carbon or nitrogen in covalent organic frameworks (COFs) or hydrogen-bonded organic frameworks (HOFs) and their derivatives, and the metal elements in specific perovskite materials (including oxide perovskites and sulfide perovskites and their derivatives), it enables the in-situ encapsulation of organic frameworks onto perovskites using perovskites as nucleation sites. This allows for the design and preparation of micro- to nanoscale perovskite / organic framework functional composite materials with a core-shell heterostructure. The introduction of the organic framework improves the light absorption capacity of the perovskite and optimizes the interfacial structure and the transport and separation properties of photogenerated charges in the composite material. This core-shell heterostructure perovskite / organic framework functional composite material is expected to form type II or S-type charge transport pathways, promoting the spatial separation and transport of photogenerated electron-hole pairs and enhancing photocatalytic reaction performance. Through the study of the structure-activity relationship of the material, the deep-seated mechanism of photocatalytic reactions is revealed, providing new insights for the rational design of advanced catalyst materials. Furthermore, this perovskite / organic framework functional composite material with a core-shell heterostructure can be used not only in the field of photocatalysis, but also is expected to be used in applications such as photoelectrocatalysis, photothermal catalysis, and piezoelectric catalysis.

[0039] In this invention, the method for effectively growing organic framework materials on perovskite using an in-situ encapsulation strategy features low temperature, short processing time, batch production capability, and adjustable shell thickness. Compared to existing improvement strategies, this method offers advantages such as tighter interfacial contact, simpler operation, and lower reaction temperature. It enables the green, rapid, and batch synthesis of perovskite / organic framework functional composite materials, solving problems such as limited sunlight utilization and poor carrier separation efficiency in perovskite materials. Furthermore, the composite material described in this invention holds promise for achieving highly efficient artificial photosynthesis of hydrogen peroxide, leading the development of photocatalyst materials.

[0040] In this invention, in perovskite / organic framework functional composite materials with a core-shell heterostructure, band matching between the perovskite and the organic framework material (including covalent organic frameworks, hydrogen-bonded organic frameworks, or their derivatives or analogs) is one of the key factors determining the photoelectric properties of the composite material. Ensuring band matching between the two materials during the design of perovskite-organic framework composites can significantly improve the composite's performance. To achieve efficient band matching, it is necessary to select perovskite and organic framework materials with matching bands. The conduction band edge of the perovskite should be lower than that of the organic framework material, while the valence band edge of the perovskite should be higher than that of the organic framework material. This combination of band structures facilitates the efficient transport of electrons from the perovskite to the organic framework material, while holes remain in the perovskite. In this way, electrons generated when the perovskite is exposed to light can be smoothly transferred to the organic framework material, while holes remain in the perovskite. Such a band structure ensures effective separation of electrons and holes, thereby improving the photoelectric properties of the composite material. This specific and ordered combination is not a random selection, but is based on a deep understanding of the material properties and a precise grasp of the band matching principle (such as Bi3TiNbO9 with C4N, BiVO3 with C4N, Bi3TiNbO9 with TpPa-COFs, etc.).

[0041] Compared with the prior art, the beneficial technical effects of the present invention are as follows: 1. The present invention provides a perovskite / organic framework functional composite material with a core-shell heterostructure and its synthesis method. Specifically, it utilizes the bonding between carbon and / or nitrogen elements in the organic framework material and metal elements in the perovskite material to in-situ encapsulate an organic framework material on the perovskite, thereby designing and preparing a batch of perovskite / organic framework micro-nano composite materials. Compared with most existing perovskite material modification methods, this method has advantages such as tight interfacial contact, simple operation, and low reaction temperature. It can achieve green, rapid, and batch synthesis of perovskite / organic framework functional composite materials, solving problems such as limited sunlight utilization and poor carrier separation efficiency of perovskite materials. Furthermore, the composite material described in this invention is expected to achieve efficient artificial photosynthesis of hydrogen peroxide, leading the development of photocatalyst materials.

[0042] 2. This invention improves the light absorption capacity of perovskite by introducing organic framework materials, optimizing the material interface structure and the transport and separation properties of photogenerated charges. The prepared perovskite / organic framework micro-nano composite material is expected to form type II or S-type charge transport pathways, promoting the spatial separation and transport of photogenerated electron-hole pairs and enhancing photocatalytic reaction performance. Through the study of the structure-activity relationship of the material, the deep-seated mechanism of photocatalytic reactions is revealed, providing new ideas for the rational design of advanced catalyst materials. Furthermore, this perovskite / organic framework composite material is not only applicable to photocatalysis but also holds promise for applications in photoelectrocatalysis, photothermal catalysis, and piezoelectric catalysis.

[0043] 3. The perovskite / organic framework functional composite material with a core-shell heterostructure of the present invention also has the characteristics of simple preparation process, readily available raw materials, excellent photocatalytic performance, and significant social and economic benefits and broad development prospects. Attached Figure Description

[0044] Figure 1 The image shows the XRD pattern of the Bi3TiNbO9@C4N composite material obtained in Example 1 of this invention.

[0045] Figure 2 This is a TEM image of the Bi3TiNbO9@C4N composite material obtained in Example 1 of the present invention.

[0046] Figure 3 The bar chart shows the photocatalytic H2O2 production performance of the materials obtained in Examples 1, 3, 4, and 5 of this invention and Comparative Examples 1 and 2.

[0047] Figure 4 The Bi4Ti3O obtained in Example 6 of this invention 12 XRD pattern of @TpPa-COFs composite material.

[0048] Figure 5 The image shows the XRD pattern of the BiVO3@C4N composite material obtained in Example 7 of this invention.

[0049] Figure 6 Photocatalytic degradation performance of tetracycline hydrochloride by the materials obtained in Examples 1, 3, 4, 5 and Comparative Examples 1, 2 for 1 hour.

[0050] Figure 7 Photocatalytic degradation performance of Rhodamine B by the materials obtained in Examples 1, 3, 4, 5 and Comparative Examples 1, 2 over 1 hour. Detailed Implementation

[0051] The technical solution of the present invention will be illustrated below with examples. The scope of protection sought by the present invention includes, but is not limited to, the following embodiments. Example 1

[0052] 2.50 g Bi₂O₃, 0.30 g TiO₂, 0.50 g Nb₂O₅, 10.50 g NaCl, 13.33 g KCl, and 2 mL anhydrous ethanol were weighed and placed in a ball mill jar. The mixture was ground clockwise and counterclockwise for 2 hours each to obtain a mixture. The mixture was then transferred to an oven and dried at 60 °C for 10 hours to obtain a mixed powder. The mixed powder was then placed in a crucible and calcined in a muffle furnace at a heating rate of 5 °C / min to 850 °C for 6 hours. Finally, the calcined solid powder was washed with deionized water until no Cl was found. - After drying, Bi3TiNbO9 powder is obtained.

[0053] Weigh 0.042 g of cyclohexanehexanone octahydrate, 0.043 g of 3,3',4,4'-benzyltetramine, and 0.014 g of the obtained Bi3TiNbO9 powder into a 100 mL beaker. Add 10 mL of N-methyl-2-pyrrolidone and 40 mL of methanol solution. After stirring for 2 h, transfer the uniformly dispersed mixture to a 100 mL polytetrafluoroethylene reaction liner and place it in a constant temperature drying oven for hydrothermal reaction at 150 °C for 12 h. After the reaction is complete, filter the resulting mixture to obtain a solid powder. Place the obtained solid powder in a Soxhlet extractor and extract with tetrahydrofuran and ethanol for 48 h to obtain a solid sample. Finally, place the obtained solid sample in a constant temperature drying oven and dry at 60 °C for 12 h to obtain a Bi3TiNbO9@C4N composite material with a molar ratio of perovskite oxide to organic framework material of approximately 1:3, denoted as Bi3TiNbO9@C4N-1:3.

[0054] Phase characterization of the Bi3TiNbO9@C4N composite material obtained in Example 1 was performed, and the results are as follows: Figure 1 As shown. By Figure 1 It can be seen that the obtained composite material contains X-ray characteristic diffraction peaks of both Bi3TiNbO9 and C4N, which are consistent with the standard card number of Bi3TiNbO9 (JCPDS No. 79-1550) and the literature of C4N (…). Small The good agreement between the results (2023, 19, 2207487) indicates that the Bi3TiNbO9@C4N composite material was successfully prepared. Figure 2 The image shows a TEM image of the prepared Bi3TiNbO9@C4N composite material. It is clearly visible from the image that, compared to Bi3TiNbO9 alone, the resulting composite material is surrounded by a layer of C4N material, further confirming the successful synthesis of the composite material. Example 2

[0055] 2.50 g Bi₂O₃, 0.30 g TiO₂, 0.50 g Nb₂O₅, 10.50 g NaCl, 13.33 g KCl, and 2 mL anhydrous ethanol were weighed and placed in a ball mill jar. The mixture was ground clockwise and counterclockwise for 2 hours each to obtain a mixture. The mixture was then transferred to an oven and dried at 60 °C for 10 hours to obtain a mixed powder. The mixed powder was then placed in a crucible and calcined in a muffle furnace at a heating rate of 5 °C / min to 850 °C for 6 hours. Finally, the calcined solid powder was washed with deionized water until no Cl was found. - After drying, Bi3TiNbO9 powder is obtained.

[0056] Weigh 0.042 g of cyclohexanehexanone octahydrate, 0.043 g of 3,3',4,4'-biphenyltetramine, and 0.083 g of the Bi3TiNbO9 powder obtained above and place them in a 100 mL beaker. Add 10 mL of N-methyl-2-pyrrolidone and 40 mL of methanol solution. After stirring for 2 h, transfer the uniformly dispersed mixture to a 100 mL polytetrafluoroethylene reaction liner and place it in a constant temperature drying oven for hydrothermal reaction at 150 °C for 12 h. After the reaction was completed, the resulting mixture was filtered to obtain a solid powder. The solid powder was then placed in a Soxhlet extractor and extracted with tetrahydrofuran and ethanol for 48 hours to obtain a solid sample. Finally, the solid sample was placed in a constant temperature drying oven and dried at 60°C for 12 hours to obtain a Bi3TiNbO9@C4N composite material with a molar ratio of perovskite oxide to organic framework material of approximately 1:0.5, denoted as Bi3TiNbO9@C4N-1:0.5. Example 3

[0057] 2.50 g Bi₂O₃, 0.30 g TiO₂, 0.50 g Nb₂O₅, 10.50 g NaCl, 13.33 g KCl, and 2 mL anhydrous ethanol were weighed and placed in a ball mill jar. The mixture was ground clockwise and counterclockwise for 2 hours each to obtain a mixture. The mixture was then transferred to an oven and dried at 60 °C for 10 hours to obtain a mixed powder. The mixed powder was then placed in a crucible and calcined in a muffle furnace at a heating rate of 5 °C / min to 850 °C for 6 hours. Finally, the calcined solid powder was washed with deionized water until no Cl was found. - After drying, Bi3TiNbO9 powder is obtained.

[0058] Weigh 0.042 g of cyclohexanehexanone octahydrate, 0.043 g of 3,3',4,4'-benzyltetramine, and 0.042 g of the obtained Bi3TiNbO9 powder into a 100 mL beaker. Add 10 mL of N-methyl-2-pyrrolidone and 40 mL of methanol solution. After stirring for 2 h, transfer the uniformly dispersed mixture to a 100 mL polytetrafluoroethylene reaction liner and place it in a constant temperature drying oven for hydrothermal reaction at 150 °C for 12 h. After the reaction is complete, filter the resulting mixture to obtain a solid powder. Place the obtained solid powder in a Soxhlet extractor and extract with tetrahydrofuran and ethanol for 48 h to obtain a solid sample. Finally, place the obtained solid sample in a constant temperature drying oven and dry at 60 °C for 12 h to obtain a Bi3TiNbO9@C4N composite material with a molar ratio of perovskite oxide to organic framework material of approximately 1:1, denoted as Bi3TiNbO9@C4N-1:1. Example 4

[0059] 2.50 g Bi₂O₃, 0.30 g TiO₂, 0.50 g Nb₂O₅, 10.50 g NaCl, 13.33 g KCl, and 2 mL anhydrous ethanol were weighed and placed in a ball mill jar. The mixture was ground clockwise and counterclockwise for 2 hours each to obtain a mixture. The mixture was then transferred to an oven and dried at 60 °C for 10 hours to obtain a mixed powder. The mixed powder was then placed in a crucible and calcined in a muffle furnace at a heating rate of 5 °C / min to 850 °C for 6 hours. Finally, the calcined solid powder was washed with deionized water until no Cl was found. - After drying, Bi3TiNbO9 powder is obtained.

[0060] Weigh 0.042 g of cyclohexanehexanone octahydrate, 0.043 g of 3,3',4,4'-benzyltetramine, and 0.021 g of the obtained Bi3TiNbO9 powder into a 100 mL beaker. Add 10 mL of N-methyl-2-pyrrolidone and 40 mL of methanol solution. After stirring for 2 h, transfer the uniformly dispersed mixture to a 100 mL polytetrafluoroethylene reaction liner and place it in a constant temperature drying oven for hydrothermal reaction at 150 °C for 12 h. After the reaction is complete, filter the resulting mixture to obtain a solid powder. Place the obtained solid powder in a Soxhlet extractor and extract with tetrahydrofuran and ethanol for 48 h to obtain a solid sample. Finally, place the obtained solid sample in a constant temperature drying oven and dry at 60 °C for 12 h to obtain a Bi3TiNbO9@C4N composite material with a molar ratio of perovskite oxide to organic framework material of approximately 1:2, denoted as Bi3TiNbO9@C4N-1:2. Example 5

[0061] 2.50 g Bi₂O₃, 0.30 g TiO₂, 0.50 g Nb₂O₅, 10.50 g NaCl, 13.33 g KCl, and 2 mL anhydrous ethanol were weighed and placed in a ball mill jar. The mixture was ground clockwise and counterclockwise for 2 hours each to obtain a mixture. The mixture was then transferred to an oven and dried at 60 °C for 10 hours to obtain a mixed powder. The mixed powder was then placed in a crucible and calcined in a muffle furnace at a heating rate of 5 °C / min to 850 °C for 6 hours. Finally, the calcined solid powder was washed with deionized water until no Cl was found. - After drying, Bi3TiNbO9 powder is obtained.

[0062] Weigh 0.042 g of cyclohexanehexanone octahydrate, 0.043 g of 3,3',4,4'-benzyltetramine, and 0.009 g of the obtained Bi3TiNbO9 powder into a 100 mL beaker. Add 10 mL of N-methyl-2-pyrrolidone and 40 mL of methanol solution. After stirring for 2 h, transfer the uniformly dispersed mixture to a 100 mL polytetrafluoroethylene reaction liner and place it in a constant temperature drying oven for hydrothermal reaction at 150 °C for 12 h. After the reaction is complete, filter the resulting mixture to obtain a solid powder. Place the obtained solid powder in a Soxhlet extractor and extract with tetrahydrofuran and ethanol for 48 h to obtain a solid sample. Finally, place the obtained solid sample in a constant temperature drying oven and dry at 60 °C for 12 h to obtain a Bi3TiNbO9@C4N composite material with a molar ratio of perovskite oxide to organic framework material of approximately 1:5, denoted as Bi3TiNbO9@C4N-1:5. Example 6

[0063] Weigh 0.079 g of C6H8O7H2O and 0.728 g of Bi(NO3)35H2O into a 50 mL beaker, then add 0.425 mL of tetrabutyl titanate, 4 mL of DMF, and 6 mL of anhydrous ethanol, and stir until the solution becomes clear. Then add 1.0 g of polyvinylpyrrolidone (PVP) and stir to dissolve, obtaining a mixture. Load the mixture into a syringe, place it in an electrospinning machine, set the electric field strength to a positive voltage of 14 kV and a negative voltage of 1.8 kV, and collect the prepared Bi4Ti3O at room temperature and a pushing speed of 0.001 cm / min. 12 Nanofibers were then formed and placed in a crucible. The crucible was heated to 500°C in a muffle furnace at a heating rate of 5°C / min, and calcined at this temperature for 6 hours to obtain Bi₄Ti₃O₃. 12 powder.

[0064] Weigh 0.064 g of p-phenylenediamine and 0.063 g of 1,3,5-tricarboxymethyl phloroglucinol into a 150 mL round-bottom flask, add 45 mL of dichloromethane, 15 mL of trichloromethane, and 0.45 mL of glacial acetic acid, and sonicate for 5 min to obtain mixed solution A; then weigh 0.060 g of the Bi4Ti3O obtained above. 12 The powder was added to mixture A and stirred at room temperature for 48 hours. After the reaction was complete, the product was washed with dichloromethane at 5000 rpm, then washed three times with anhydrous ethanol by centrifugation. The mixture was then filtered to obtain a solid sample. Finally, the solid sample was dried in a vacuum oven at 60°C for 12 hours to obtain Bi4Ti3O4 with a perovskite oxide to organic framework material molar ratio of approximately 1:1. 12 @TpPa-COFs composite material.

[0065] Bi4Ti3O synthesized in Example 6 12 Phase characterization of the / TpPa-COFs composite material was performed, and the results are as follows: Figure 4 As shown. By Figure 4 It can be seen that the obtained composite material contains Bi4Ti3O 12 The X-ray characteristic diffraction peaks of TpPa-COFs materials, and their similarity to Bi4Ti3O 12 The standard card number (JCPDS No. 80-2143) and TpPa-COFs are consistent with the literature ( Chem. Eng. J. The results (2022, 444, 136584) are basically consistent, indicating that the Bi4Ti3O 12 @TpPa-COFs composite materials were successfully prepared. Example 7

[0066] Weigh 2.21 g BiCl3, 1.05 g hexadecyltrimethylammonium bromide, and 2.80 g NaVO3 into a 100 mL beaker, add 60 mL of ethylene glycol solution, and stir for 1 h. Then, transfer the well-dispersed mixture into a 100 mL polytetrafluoroethylene reaction liner and place it in a constant temperature drying oven for hydrothermal reaction at 120 °C for 12 h. After the reaction is complete, filter the resulting mixture to obtain a solid powder. Wash the solid powder with anhydrous ethanol and deionized water, and then dry it in a vacuum drying oven at 60 °C for 12 h to obtain a solid powder. Finally, place the solid powder in a crucible and calcine it in a muffle furnace at a heating rate of 8 °C / min to 400 °C for 4 h to obtain BiVO4 powder.

[0067] Weigh 0.042 g of cyclohexanehexanone octahydrate, 0.043 g of 3,3',4,4'-benzyltetramine, and 0.064 g of the obtained BiVO4 powder into a 100 mL beaker. Add 10 mL of N-methyl-2-pyrrolidone and 40 mL of methanol solution. After stirring for 2 h, transfer the uniformly dispersed mixture to a 100 mL polytetrafluoroethylene reaction liner and place it in a constant temperature drying oven for hydrothermal reaction at 150 °C for 12 h. After the reaction is complete, filter the resulting mixture to obtain a solid powder. Place the obtained solid powder in a Soxhlet extractor and extract with tetrahydrofuran and ethanol for 48 h to obtain a solid sample. Finally, place the obtained solid sample in a constant temperature drying oven and dry at 60 °C for 12 h to obtain a BiVO4@C4N composite material with an oxide perovskite to organic framework material molar ratio of approximately 1:1, denoted as BiVO4@C4N-1:1.

[0068] The phase characterization of the BiVO4@C4N composite material synthesized in Example 7 was performed, and the results are as follows: Figure 5 As shown. By Figure 5 It can be seen that the obtained composite material exhibits the characteristic X-ray diffraction peaks of BiVO4 and C4N materials, and its standard card number (JCPDS No. 14-0688) for BiVO4 and its literature number (JCPDS No. 14-0688) for C4N are consistent with those of BiVO4 and C4N, respectively. Small The results (2023, 19, 2207487) are basically consistent, indicating that the BiVO4@C4N composite material was successfully prepared. Example 8

[0069] Weigh 0.013g Ba(NO3)2 and 0.006g L-cysteine ​​into an 80mL beaker, add 22mL ethylene glycol, and stir for 1.5h to obtain mixture A; weigh 0.016g ZrOCl2·8H2O and 0.013g thiourea into a double-jacketed beaker in a cell disruptor, add 22mL ethylene glycol and 100μL hydrazine hydrate, and mix for 35min to obtain mixture B; then add all of mixture B into mixture A, mix evenly to obtain mixture C; transfer the evenly dispersed mixture to a 100mL polytetrafluoroethylene reaction liner, and place it in a constant temperature drying oven for hydrothermal reaction at 220℃ for 24h. After the reaction was completed, the product was washed with deionized water at 6000 rpm until the upper liquid became clear. Then, it was washed 6 times by centrifugation with anhydrous ethanol. The mixture was then filtered to obtain a solid sample. Finally, the solid sample was placed in a vacuum oven and dried at 75°C for 5 hours to obtain BaZrS3 powder.

[0070] Weigh 0.042 g of cyclohexanehexanone octahydrate, 0.043 g of 3,3',4,4'-benzyltetramine, and 0.064 g of the obtained BaZrS3 powder and place them in a 100 mL beaker. Add 10 mL of N-methyl-2-pyrrolidone and 40 mL of methanol solution. After stirring for 2 h, transfer the uniformly dispersed mixture to a 100 mL polytetrafluoroethylene reaction liner and place it in a constant temperature drying oven for hydrothermal reaction at 150 °C for 12 h. After the reaction is complete, filter the resulting mixture to obtain a solid powder. Place the obtained solid powder in a Soxhlet extractor and extract with tetrahydrofuran and ethanol for 48 h to obtain a solid sample. Finally, place the obtained solid sample in a constant temperature drying oven and dry at 60 °C for 12 h to obtain a BaZrS3@C4N composite material with a sulfide perovskite to organic framework material molar ratio of approximately 1:1, denoted as BaZrS3@C4N-1:1. Example 9

[0071] 0.013 g Ba(NO3)2 and 0.018 g L-cysteine ​​were weighed and placed in an 80 mL beaker. 22 mL of ethylene glycol was added, and the mixture was stirred for 1.5 h to obtain mixture A. 0.014 g tetrabutyl titanate was weighed and placed in a double-jacketed beaker in a cell disruptor. 22 mL of ethylene glycol and 100 μL of hydrazine hydrate were added, and the mixture was treated for 35 min to obtain mixture B. Mixture B was then added to mixture A and mixed thoroughly to obtain mixture C. The uniformly dispersed mixture was transferred to a 100 mL polytetrafluoroethylene reaction liner and placed in a constant temperature drying oven for hydrothermal reaction at 220 °C for 24 h. After the reaction was completed, the product was washed with deionized water at 6000 rpm until the upper liquid became clear. Then, it was washed 6 times by centrifugation with anhydrous ethanol. The mixture was then filtered to obtain a solid sample. Finally, the solid sample was dried in a vacuum oven at 75 °C for 5 h to obtain BaTiS3 material.

[0072] Weigh 0.042 g of cyclohexanehexanone octahydrate, 0.043 g of 3,3',4,4'-benzyltetramine, and 0.056 g of the obtained BaTiS3 powder into a 100 mL beaker. Add 10 mL of N-methyl-2-pyrrolidone and 40 mL of methanol solution. After stirring for 2 h, transfer the uniformly dispersed mixture to a 100 mL polytetrafluoroethylene reaction liner and place it in a constant temperature drying oven for hydrothermal reaction at 150 °C for 12 h. After the reaction is complete, filter the resulting mixture to obtain a solid powder. Place the obtained solid powder in a Soxhlet extractor and extract with tetrahydrofuran and ethanol for 48 h to obtain a solid sample. Finally, place the obtained solid sample in a constant temperature drying oven and dry at 60 °C for 12 h to obtain a BaTiS3@C4N composite material with a sulfide perovskite to organic framework material molar ratio of approximately 1:1, denoted as BaTiS3@C4N-1:1. Example 10

[0073] 2.50 g Bi₂O₃, 0.30 g TiO₂, 0.50 g Nb₂O₅, 10.50 g NaCl, 13.33 g KCl, and 2 mL anhydrous ethanol were weighed and placed in a ball mill jar. The mixture was ground clockwise and counterclockwise for 2 hours each to obtain a mixture. The mixture was then transferred to an oven and dried at 60 °C for 10 hours to obtain a mixed powder. The powder was then placed in a crucible and calcined in a muffle furnace at a heating rate of 5 °C / min to 850 °C for 6 hours. Finally, the calcined solid powder was washed with deionized water until no Cl⁻ remained and dried to obtain Bi₃TiNbO₉ powder.

[0074] Weigh 50 mg of 1,3,6,8-tetra(4-carboxyphenyl)pyrene into a 100 mL beaker, add 10 mL of DMF, 27 mL of methanol, 14 mL of water, and 0.067 g of the Bi3TiNbO9 powder obtained above, stir for 1 h to obtain a mixture, and filter the mixture to obtain a solid powder. Wash the obtained solid powder three times with methanol; finally, dry the obtained solid sample in a constant temperature drying oven for 12 h to obtain Bi3TiNbO9@HOF-PFC-1 material with a molar ratio of perovskite oxide to organic framework material of approximately 1:1. Example 11

[0075] 2.50 g Bi₂O₃, 0.30 g TiO₂, 0.50 g Nb₂O₅, 10.50 g NaCl, 13.33 g KCl, and 2 mL anhydrous ethanol were weighed and placed in a ball mill jar. The mixture was ground clockwise and counterclockwise for 2 hours each to obtain a mixture. The mixture was then transferred to an oven and dried at 60 °C for 10 hours to obtain a mixed powder. The powder was then placed in a crucible and calcined in a muffle furnace at a heating rate of 5 °C / min to 850 °C for 6 hours. Finally, the calcined solid powder was washed with deionized water until no Cl⁻ remained and dried to obtain Bi₃TiNbO₉ powder.

[0076] 0.016 g of p-phenylenediamine and 0.017 g of 1,3,5-tricarboxymethyl phloroglucinol were weighed and placed in a 50 mL round-bottom flask. 12 mL of dichloromethane, 4 mL of trichloromethane, and 0.15 mL of glacial acetic acid were added, and the mixture was sonicated for 5 min to obtain mixed solution A. Then, 0.068 g of the previously obtained Bi3TiNbO9 powder was weighed and added to mixed solution A, and the mixture was stirred at room temperature for 48 h. After the reaction was complete, the product was washed with dichloromethane at 5000 rpm, then washed three times with anhydrous ethanol by centrifugation. The mixture was then filtered to obtain a solid sample. Finally, the solid sample was dried in a vacuum oven at 60 °C for 12 h to obtain a Bi3TiNbO9@TpPa-COFs composite material with a perovskite oxide to organic framework material molar ratio of approximately 1:1. Example 12

[0077] Weigh 0.011g Sr(NO3)2 and 0.018g L-cysteine ​​into an 80mL beaker, add 22mL ethylene glycol, and stir for 1.5h to obtain mixture A; weigh 0.016g ZrOCl2·8H2O into a double-jacketed beaker in a cell disruptor, add 22mL ethylene glycol and 100μL hydrazine hydrate, and mix for 35min to obtain mixture B; then add all of mixture B into mixture A, mix well to obtain mixture C; transfer the well-dispersed mixture to a 100mL polytetrafluoroethylene reaction liner, and place it in a constant temperature drying oven for hydrothermal reaction at 220℃ for 24h. After the reaction was completed, the product was washed with deionized water at 6000 rpm until the upper liquid became clear, and then washed 6 times with anhydrous ethanol by centrifugation. The mixture was then filtered to obtain a solid sample. Finally, the solid sample was placed in a vacuum oven and dried at 75°C for 5 hours to obtain SrZrS3 material.

[0078] 0.064 g of p-phenylenediamine and 0.063 g of 1,3,5-tricarboxymethyl phloroglucinol were weighed and placed in a 150 mL round-bottom flask. 45 mL of dichloromethane, 15 mL of trichloromethane, and 0.45 mL of glacial acetic acid were added, and the mixture was sonicated for 5 min to obtain mixed solution A. Then, 0.057 g of the previously obtained SrZrS3 powder was weighed and added to mixed solution A, and the mixture was stirred at room temperature for 48 h. After the reaction was complete, the product was washed with dichloromethane at 5000 rpm, then washed three times with anhydrous ethanol by centrifugation. The mixture was then filtered to obtain a solid sample. Finally, the solid sample was dried in a vacuum oven at 60 °C for 12 h to obtain a SrZrS3@TpPa-COFs composite material with a sulfide perovskite to organic framework material molar ratio of approximately 1:1.

[0079] Comparative Example 1 2.50 g Bi₂O₃, 0.30 g TiO₂, 0.50 g Nb₂O₅, 10.50 g NaCl, 13.33 g KCl, and 2 mL anhydrous ethanol were weighed and placed in a ball mill jar. The mixture was ground clockwise and counterclockwise for 2 hours each to obtain a mixture. The mixture was then transferred to an oven and dried at 60 °C for 10 hours to obtain a mixed powder. The mixed powder was then placed in a crucible and calcined in a muffle furnace at a heating rate of 5 °C / min to 850 °C for 6 hours. Finally, the calcined solid powder was washed with deionized water until no Cl was found. - After drying, Bi3TiNbO9 material is obtained.

[0080] Comparative Example 2 Weigh 0.042 g of cyclohexanehexanone octahydrate, 0.043 g of 3,3',4,4'-benzyltetramine, and 0.009 g of the obtained Bi3TiNbO9 powder into a 100 mL beaker. Add 10 mL of N-methyl-2-pyrrolidone and 40 mL of methanol solution. After stirring for 2 h, transfer the uniformly dispersed mixture to a 100 mL polytetrafluoroethylene reaction liner and place it in a constant temperature drying oven for hydrothermal reaction at 150 °C for 12 h. After the reaction is complete, filter the resulting mixture to obtain a solid powder. Place the obtained solid powder in a Soxhlet extractor and extract with tetrahydrofuran and ethanol for 48 h to obtain a solid sample. Finally, place the obtained solid sample in a constant temperature drying oven and dry at 60 °C for 12 h to obtain the C4N material.

[0081] Comparative Example 3 The Bi3TiNbO9 material prepared in Comparative Example 1 and the C4N material prepared in Comparative Example 2 were mixed in a molar ratio of 1:1 to obtain a mixed material.

[0082] Application Examples

[0083] Photocatalytic preparation of H2O2: 0.005 g of each of the materials prepared in Examples 1-12 and Comparative Examples 1-3 were weighed and placed in different beakers. 20 mL of deionized water was added to each beaker. After uniform dispersion, dry air was introduced and the mixture was stirred for 1 hour. Finally, the resulting mixture was placed under simulated sunlight for photocatalytic reaction. After the reaction was completed, the mixture was filtered with a filter and the filtrate was collected. 1 mL of the filtrate was then placed in a centrifuge tube. 3 mL of 0.001 mol / L cerium sulfate and 7 mL of 0.15 mol / L sulfuric acid solution were then added to the centrifuge tube for reaction. Finally, the absorbance was measured using a UV-Vis spectrophotometer to evaluate the photocatalytic H2O2 production performance of the prepared material.

[0084] Photocatalytic degradation of tetracycline hydrochloride: 0.01 g of each of the materials prepared in Examples 1-12 and Comparative Examples 1-3 were weighed and placed in a photoreactor. 20 mL of tetracycline hydrochloride solution was added, and the mixture was stirred and dispersed evenly. After stirring in the dark for 1 hour, the xenon lamp power was turned on to carry out the photocatalytic reaction for 1 hour. After the reaction was completed, the mixture was filtered through a filter and the filtrate was collected. Then, 10 mL of the filtrate was measured and placed in a centrifuge tube. Finally, the absorbance was measured using a UV-Vis spectrophotometer to determine the photocatalytic degradation performance of the material for tetracycline.

[0085] Photocatalytic degradation of Rhodamine B: 0.01 g of each of the materials prepared in Examples 1-12 and Comparative Examples 1-3 were weighed and placed in a photoreactor. 20 mL of Rhodamine B solution was added, and the mixture was stirred and dispersed evenly. After stirring in the dark for 1 hour, the xenon lamp power was turned on to allow for photocatalytic degradation of Rhodamine B for 1 hour. After the reaction was complete, the mixture was filtered through a filter and the filtrate was collected. 10 mL of the filtrate was then measured and placed in a centrifuge tube. Finally, the absorbance was measured using a UV-Vis spectrophotometer to determine the photocatalytic degradation performance of the material against Rhodamine B.

[0086] The photocatalytic performance of the composite materials obtained in Examples 1-12 of this invention is compared with that of the materials obtained in Comparative Examples 1-3 in the following table:

[0087] As can be seen from the table above, in this invention, through the organic combination of special perovskite materials and specific organic framework materials, the overall photocatalytic performance of the composite materials prepared by this invention is significantly better than that of composite materials obtained by simply mixing perovskite materials, single organic framework materials, or simple physical mixing of perovskite materials and organic framework materials. Furthermore, the composite materials of this invention are bonded by chemical bonds or coordination bonds, resulting in a longer service life and easier recycling. In particular, they possess outstanding and unique advantages in the photocatalytic synthesis of H2O2, photocatalytic degradation of antibiotics or dye molecules, photocatalytic formaldehyde oxidation, photocatalytic H2 production, and photocatalytic CO2 reduction, and are expected to provide new research directions and corresponding theoretical research basis for the long-term development of photocatalyst materials.

[0088] In this invention, the reagents used in the above embodiments and comparative examples are all derived from commercially available products, including:

[0089]

[0090] The sources of the above-mentioned drugs and reagents are not limited to the aforementioned enterprises or units; identical commercially available products purchased through other legal channels are also acceptable. The sources of the above-mentioned drugs and reagents should not be considered as a limitation on the scope of protection claimed in this invention.

Claims

1. A photocatalytic material with a core-shell heterostructure, characterized in that: The photocatalytic material comprises a core material and a shell layer encasing the core material: The photocatalytic material is Bi3TiNbO9@C4N or Bi4Ti3O 12 One or more of @TpPa-COFs, BaZrS3@C4N, BaTiS3@C4N, Bi3TiNbO9@HOF-PFC-1, Bi3TiNbO9@TpPa-COFs, and SrZrS3@TpPa-COFs.

2. The photocatalytic material according to claim 1, characterized in that: In the photocatalytic material, the composite molar ratio of the core material to the shell is 1:0.5~10.

3. The photocatalytic material according to claim 2, characterized in that: In the photocatalytic material, the composite molar ratio of the core material to the shell is 1:1 to 8.

4. The photocatalytic material according to claim 3, characterized in that: In the photocatalytic material, the composite molar ratio of the core material to the shell is 1:2~5.

5. The photocatalytic material according to claim 3 or 4, characterized in that: The particle size of the photocatalytic material is 0.1~10μm.

6. The photocatalytic material according to claim 5, characterized in that: The particle size of the photocatalytic material is 0.3~8μm.

7. The photocatalytic material according to claim 6, characterized in that: The particle size of the photocatalytic material is 0.5~5μm.

8. A method for preparing a photocatalytic material having a core-shell heterostructure as described in any one of claims 1-7, characterized in that: The method includes: 1) Prepare a shell precursor solution according to the specific composition of C4N, TpPa-COFs or HOF-PFC-1 used as the shell. 2) Add Bi3TiNbO9 and Bi4Ti3O9 as core materials to the above shell precursor solution. 12 BaZrS3, BaTiS3 or SrZrS3 are dispersed evenly and then reacted. After the reaction is completed, the resulting solid product is purified and dried to obtain the target photocatalytic material. Step 1) Specifically includes: Preparation of C4N precursor solution: Cyclohexane hexahydrate, 3,3',4,4'-biphenyltetramine are placed in a beaker according to the proportion, N-methyl-2-pyrrolidone and methanol solution are added, and after stirring and mixing evenly, the C4N precursor solution is obtained. Preparation of TpPa-COFs precursor solution: P-phenylenediamine and 1,3,5-tricarboxymethyl phloroglucinol were placed in a round-bottom flask in proportion, and dichloromethane, trichloromethane and glacial acetic acid were added and mixed evenly to obtain TpPa-COFs precursor solution. Preparation of HOF-PFC-1 precursor solution: 1,3,6,8-tetra(4-carboxyphenyl)pyrene was placed in a beaker and solvent was added. After stirring evenly, HOF-PFC-1 precursor solution was obtained. In step 2), the amount of core material added is such that Bi3TiNbO9 and Bi4Ti3O 12 The molar ratio of BaZrS3, BaTiS3 or SrZrS3 to C4N, TpPa-COFs or HOF-PFC-1 is 1:0.8~12; the reaction temperature is 100~300℃, and the reaction time is 2~48h.

9. The method according to claim 8, characterized in that: In step 2), the amount of core material added is such that Bi3TiNbO9 and Bi4Ti3O 12 The molar ratio of BaZrS3, BaTiS3 or SrZrS3 to C4N, TpPa-COFs or HOF-PFC-1 is 1:1.2~10; In step 2), the reaction temperature is 120~250℃; the reaction time is 5~36h.

10. The method according to claim 9, characterized in that: In step 2), the amount of core material added is such that Bi3TiNbO9 and Bi4Ti3O 12 The molar ratio of BaZrS3, BaTiS3 or SrZrS3 to C4N, TpPa-COFs or HOF-PFC-1 is 1:2.2~8; In step 2), the reaction temperature is 150~200℃; the reaction time is 8~24h.

11. The use of a photocatalytic material with a core-shell heterostructure as described in any one of claims 1-7, or the use of a photocatalytic material with a core-shell heterostructure prepared by the method described in any one of claims 8-10, characterized in that: The photocatalytic material with the core-shell heterostructure is used for photocatalytic synthesis of H2O2, photocatalytic degradation of antibiotic or dye molecules, photocatalytic oxidation of formaldehyde, photocatalytic production of H2, or photocatalytic reduction of CO2.

Citation Information

Patent Citations

  • Preparation method and application of core-shell BiFeO3-coated TpPa-1-COF piezoelectric photocatalyst

    CN115041231A